Φώτης Κόντογλου - Ηλίας Μπογδανόπουλος: δύο υπέρμαχοι της μονοφωνικής εκκλησιαστικής μουσικής - ΚΑΠΚΙΔΗ, Μαρία (Byzantina Symmeikta, 2020)
Fotis Kontoglou – Elias Bogdanopoulos: Two Proponents of Monophonic Ecclesiastical Music The paper examines the unknown correspondence between Fotis Kontoglou and Elias Bogdanopoulos. The two men maintained a special relationship with ecclesiastical byzantine music. Kontoglou was a famous and very talented Greek hagiographer, as well as an author. He was born in 1895 in Aivali, Asia Minor and died in 1965 in Athens after a car accident which happened in 1963. His archive was presented in 2014 by his two grandchildren to the Byzantine Museum in Athens where it is open to everybody for study and research. New documents still enrich Kontoglou’s archive like the above mentioned correspondence with Elias Bogdanopoulos, a lawyer and hymnographer from Patras. Their letters were written between 1960 and 1963 and their main subject was monophonic byzantine music. Both of them were fanatic opponents of the polyphonic –western type– chanting in Christian Orthodox Greek churches. So, their articles and letters are talking about the harmony of byzantine arts generally and especially of the monophonic –eastern chanting– in Athen’s churches.